Fiscal Structures and Economic Sustainability in the EU Member States: Challenges and Opportunities - Ionascu, Alina Elena; Olteanu Burca, Andreea Larisa (The Journal of Accounting and Management, 2025)
This study analyzes the structure and evolution of personal income tax and social contributions across the European Union (EU) and the Eurozone. Tax revenue, derived from direct taxes (e.g., personal income tax, corporate tax) and indirect taxes (e.g., VAT, excises), alongside social contributions, plays a crucial role in financing public services and infrastructure. The study primarily relies on the analysis of publicly available data, observation, and comparative assessment to identify differences in tax burdens and their impact on economic and social systems. Additionally, it includes a review of fiscal policies across EU countries.The findings reveal significant disparities among member states in tax burdens and fiscal policies, influenced by economic priorities and social welfare models. This study provides valuable insights for academics, researchers and policymakers by analyzing tax structures and fiscal policies in the EU. It highlights differences in tax burdens, their economic and social implications, and policy trends such as digitalization and post-pandemic fiscal adjustments. The key contribution of the paper lies in its comprehensive data-driven analysis, combining quantitative tax data with a comparative policy review. Additionally, it offers timely insights into recent fiscal changes, making it a relevant resource for future tax policy planning. This study analyzes the structure and evolution of personal income tax and social contributions across the European Union (EU) and the Eurozone. Tax revenue, derived from direct taxes (e.g., personal income tax, corporate tax) and indirect taxes (e.g., VAT, excises), alongside social contributions, plays a crucial role in financing public services and infrastructure. The study primarily relies on the analysis of publicly available data, observation, and comparative assessment to identify differences in tax burdens and their impact on economic and social systems. Additionally, it includes a review of fiscal policies across EU countries.The findings reveal significant disparities among member states in tax burdens and fiscal policies, influenced by economic priorities and social welfare models. This study provides valuable insights for academics, researchers and policymakers by analyzing tax structures and fiscal policies in the EU. It highlights differences in tax burdens, their economic and social implications, and policy trends such as digitalization and post-pandemic fiscal adjustments. The key contribution of the paper lies in its comprehensive data-driven analysis, combining quantitative tax data with a comparative policy review. Additionally, it offers timely insights into recent fiscal changes, making it a relevant resource for future tax policy planning.